Critical viewpoints on the Bologna Process in Europe: Can we do otherwise?. (March 2019) - Wihlborg, Monne
The starting point for this inductive study is to determine, through a search of studies, what critical viewpoints in terms of research are delivered, based on experiences, observations and evaluation, concerning the Bologna Process over time? The aim is to present a description using a thematic analysis based on data from 38 papers (2004–2016) that reveal the critical reasoning behind the research. The reasoning is critical in the sense that various authors have elaborated on and problematized aspects of the Bologna Process in terms of what to avoid and/or have characterized aspects related to the Bologna Process that are not desirable. Based on the outcome of the thematic analysis, theorists were selected in order to deepen the reasoning and meaning highlighted in three themes. The findings are further discussed in terms of knowledge and curriculum development for the future and the advancement of European higher education policy and beyond on equal terms. The article suggests that there are causes for concern regarding unwanted consequences in the aftermath of the Bologna Process.